Impact of living arrangements and internet use on the mental health of Chinese older adults - Zhong, Ruyu; Ning, Wenwen (Frontiers in Public Health, 2024)
IntroductionThe consequences of aged living arrangements on mental health in the digital age have drawn significant research attention.MethodsThis study used empirical data to analyze the impact of living arrangements on the mental health of older adults by ordinary least squares (OLS) and to examine the moderating effect of Internet use in it through the moderating effect test. A total of 17,243 older adults were included in the analytical model.ResultsWe found that living independently has a negative impact on the mental health of older adults and Internet use can improve the mental health of older adults. There are moderating mechanisms of Internet use in the impact of living arrangements on the mental health of older adults, but it is necessary to look at the moderating mechanisms of different patterns of Internet use. Using the Internet for social interaction (chatting and information acquisition) can weaken the impact of living arrangements on the mental health of older adults, while unidirectional Internet use (entertainment and financial management) strengthens the impact of living arrangements on the mental health of older adults.DisscusionTherefore, this study puts forward the following suggestions: first, to develop family care for older adults and pay attention to the positive role of intergenerational support in the mental comfort of older adults; second, it is imperative for the government and social service departments to assist older adults in establishing correct concepts of Internet use, enhancing their digital literacy, and improving their digital skills.